MANAJEMEN PENDIDIKAN ISLAM BERBASIS GLOKALISASI PADA LEMBAGA PENDIDIKAN ISLAM: STUDI KASUS PADA YAYASAN GENERASI MADANI BANTEN - Kasronudin; Fahmi Hauzan Rafif; Iskandar Balad; Ahmad Suryadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the model of Islamic education management based on glocalization in contemporary Islamic educational institutions, with a case study at the Generasi Madani Banten Foundation, which manages three educational units: TKIT Generasi Madani, SDIT Peradaban Mulia, and SMP Islam Al-Bashri Boarding School. The phenomenon of globalization brings a dual challenge: westernization, which tends to be secularistic, and the urgency of indigenization, which seeks to strengthen local identity. This research employs a qualitative approach with a descriptive-analytical case study method. Data were collected through in-depth interviews, observation, and documentation study, then analyzed using data condensation, data display, and conclusion drawing. The results indicate that the Generasi Madani Banten Foundation systematically integrates three main dimensions: the global dimension (digitalization, 21st-century competencies, foreign languages), the local dimension (Banten's cultural wisdom and community empowerment), and the Islamic dimension (aqidah, worship, morals, and Quranic memorization/tahfiz). This integration is manifested through comprehensive management functions, ranging from strategic planning, trust-based (amanah) organizing, integrated curriculum implementation, to holistic quality evaluation. This study concludes that glocalization-based management successfully positions Islamic educational institutions as competitive global agents of modernization while firmly maintaining their Islamic character and local cultural roots.